Spontaneous Perforation of Common Bile Duct: A Rare Presentation of Gall Stones Disease - Duminda Subasinghe; Edippuli Arachchige Don Udayakumara; Upul Somathilaka; Milinda Huruggamuwa (Case Reports in Gastrointestinal Medicine)
Background. Spontaneous perforation of the extrahepatic biliary system is a rare presentation of gall stones. Very few cases of bile duct perforation have been reported in adults. It is rarely suspected or correctly diagnosed preoperatively. Case Presentation. A 66-year-old female presented at the surgical emergency with 3 days’ history of severe upper abdominal pain with distension and repeated episodes of vomiting, as she had evidence of generalized peritonitis and underwent an exploratory laparotomy. A single 0.5 cm × 0.5 cm free perforation was present on the anterolateral surface of the common bile duct at the junction of cystic duct. A cholecystectomy and the CBD exploration were performed. Conclusion. Spontaneous perforation of the extrahepatic bile duct is a rare but important presentation of gall stones in adults. Therefore, awareness of the clinical presentation, expert ultrasound examination, and surgery are important aspects in the management.